Oxidative alterations in exfoliated oral mucosa cells of patients with major depressive disorder - Lukas Mendes de Abreu; Cintia Rodrigues da Silva; Ana Laura Ferreira Bortoleto; Giovana Barros Nunes; Matheus Martins Gracia; Rafael Akira Tzanno Murayama; Daniel Galera Bernabé; Gisele Zoccal Mingoti (Journal of Oral Biology and Craniofacial Research)
Objectives: This study aimed to investigate oxidative stress markers in the oral mucosal cells of individuals diagnosed with major depressive disorder (MDD). Methods: A case-control design was used, including twenty patients diagnosed with MDD, based on the Diagnostic and Statistical Manual of Mental Disorders (DSM-5) criteria, and twenty healthy controls. Oral exfoliated cells were collected from all participants. Intracellular levels of reactive oxygen species (ROS), mitochondrial membrane potential (ΔΨm), caspase-3 and -7 activity, and reduced glutathione (GSH) were measured in Arbitrary Fluorescence Units (AFU). Results: The MDD group demonstrated significantly elevated intracellular ROS levels (p = 0.0012) and caspase-3 and -7 activity (p = 0.0171) in comparison to the control group. Additionally, a decrease in ΔΨm expression was observed in the oral cells of MDD patients (p = 0.0265), whereas GSH expression levels did not differ significantly between the two groups (p = 0.8908). Conclusions: The findings indicate heightened oxidative stress in the oral exfoliated cells of individuals with MDD. This study supports the potential use of oral cells as a non-invasive biomarker source for assessing oxidative stress in depressive disorders.